Crystallization and preliminary crystallographic studies of dihydrofolate reductase-thymidylate synthase from Trypanosoma cruzi, the Chagas disease pathogen - Penchit Chitnumsub (2018)
Trypanosoma cruzi dihydrofolate reductase-thymidylate synthase (TcDHFR-TS) was crystallized in complexes with the dihydrotriazine-based or quinazoline-based antifolates C-448, cycloguanil (CYC) and Q-8 in order to gain insight into the interactions of this DHFR enzyme with classical and novel inhibitors. The TcDHFR-TS-C-448-NDP-dUMP crystal belonged to space group C2221 with two molecules per asymmetric unit and diffracted to 2.37 Å resolution. The TcDHFR-TS-CYC, TcDHFR-TS-CYC-NDP and TcDHFR-TS-Q-8-NDP crystals belonged to space group P21 with four molecules per asymmetric unit and diffracted to 2.1, 2.6 and 2.8 Å resolution, respectively. Crystals belonging to the two different space groups were suitable for structure determination. © 2009 International Union of Crystallography. All rights reserved.